Mineral scale formation and mitigation on metals and a polymeric heat exchanger surface - Kazi, S.N.; Duffy, G.G.; Chen, X.D. (Elsevier, 2010)
An experimental set-up was built to study heat transfer fouling of different pipe materials used in heat exchangers. Fouling mitigation investigations using wood pulp fibres in suspension in the fouling liquid were also performed. The new set-up allows progressive visual observation of fouling with time together with a recorded history under the same solution conditions. On completion, the tube under investigation could be removed to obtain quantitative data on the progressive build up of the deposit as well as the composition of the deposit. The experimental technique involved a pipe test specimen being centrally located in a cylindrical tank concentric with a vertical agitator to give constant and uniform flow conditions near the tube surface. The investigation of calcium sulphate deposition on four different metal surfaces (copper, aluminium, brass and stainless steel SS 316 respectively) and a polycarbonate surface reveals that the fouling increases with time but at a decreasing rate. The deposition on a metal surface can be seen to increase with increasing thermal conductivity and decreasing total surface energy over the range of experiments. Low surface energy material such as polycarbonate causes less attraction to the floating crystals and receives less deposition in comparison to the SS surface. Bleached Kraft softwood fibres at various concentrations were added to the solution to examine their effects on fouling. The results indicate that fouling is reduced as fibre concentration increases. It was also found that the fouling on stainless steel, brass and copper surfaces were all retarded in presence of fibre in the solution. (C) 2010 Elsevier Ltd. All rights reserved.